STUDI PENINGKATAN MUTU PELAYANAN DI BALAI LATIHAN KERJA (BLK) KABUPATEN MAGELANG DENGAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) - Wibisono, Adnan (Jurnal Nosel, 2015)
The purpose of this study was to determine the improvement of service quality in BLK Magelang regency. The method of Quality Function Deployment (QFD) in an effort to improve its services, especially in the automotive field. This research was conducted in BLK Magelang, Central Java Province. This study is a survey with a sample of 48 respondents research with a total sampling. Data collection techniques in this research through interviews, observation, questionnaire, literature, and documentation. Hypothesis testing using t-test mean difference in the two right hands with a significance level of 5%. The results of this study that: 1) Improving the quality of service in Magelang regency BLK the method of Quality Function Deployment (QFD) through 18 consumer voice (voice of customer). Of 18 votes, based on the results of the CRS normalization can be seen there are 5 highest percentage values of 12.6%; 11.4%; 11.3%; 9.3%; and 9.3%. This fifth respectively are: Structuring a regular room, teachers are competent, service is available during business hours, neatness and cleanliness of the teachers, and the training schedule implemented on time, 2) Some things to consider institutions as technical requirements to improve service trainee security is guaranteed, the customer service is reached, teachers look neat, professional employees, the target is reached on time, 3) Based on QFD that the targets to be met to improve the quality of service is the professionalism of employees (1,305), Ease of consumers to obtain information (1,269), neatness of employees (1,21), professionalism of teachers (1,208), and the customer service is reached (1.18).